DESCRIPTION ANXIETY LEVEL OF PULMONARY TB PATIENTS - Aini, Dwi Nur; Arifianto, Arifianto; Arifianto, Arifianto (Universitas Widya Husada, 2020)
Pulmonary tuberculosis is a disease caused by mycobacterium tuberculosis, which is an aerobic germ that can live mainly in the lungs or in various other organs that have high oxygen partial pressure The purpose of this study was to description anxiety levels of pulmonary TB patients in Salatiga General Hospital. This study uses quantitative research with a descriptive method. Research instruments using questionnaire. The sample technique used is Purposive Sampling Technique. The population is 164 respondents and the sample size is 44 respondents. The results of this study found the age of the respondents at most with an age range of 31-50 years, which is as much as 25 respondents (56.6%), the sex of the respondents most with the female gender, namely as many as 25 respondents (56.8%), the education level of respondents the most number of elementary school education is as many as 27 respondents (61.7%), the most anxiety level of respondents with moderate anxiety, which is as much as 22 respondents (50%).